Base‐Mediated Remote Deuteration of N‐Heteroarenes – Broad Scope and Mechanism. Issue 19 (1st April 2022) - Kopf, Sara; Liu, Jiali; Franke, Robert; Jiao, Haijun; Neumann, Helfried; Beller, Matthias
Abstract: Deuterated organic molecules provide the basis for many applications in life sciences and material research. Thus, methodologies to access labeled compounds with defined selectivity continue to be important. Using KO t Bu as base and DMSO‐ d 6 as deuterium source, we present a general and applicable method for the selective deuteration of a set of nitrogen‐containing heterocycles (pyridines, azines and bioactive molecules). Experimental and DFT mechanistic studies indicate that this reaction proceeds via deprotonation of the substrates by the dimsyl anion. The relative thermodynamic stability of the heterocycle anions determines the distribution and degree of deuteration. Abstract : Labeling the remote sites of pyridines for drug discovery and mechanistic applications is a challenge that can be overcome by submitting heteroaromatic substrates to a base‐mediated deuteration procedure using a combination of potassium tert ‐butoxide and deuterated DMSO. According to DFT investigations, the selectivity is controlled by the thermodynamic stability of the intermediary pyridyl anions.